Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find $x,y,z \in \Bbb Z, 1<x<y<z$ and $xyz - 1 = t(x-1)(y-1)(z-1)$.

Help me!

share|cite|improve this question
What values does $t$ take? – T. Eskin Feb 25 '13 at 15:07
If OP's $t$ is an integer it has to range between 1 to 3 given the conditions. – Vincent Tjeng Feb 25 '13 at 15:50
@VincentTjeng please show us how you deduced that. – franklin Mar 7 '13 at 2:27
Hi @franklin, my bound can be found below as an answer. It was a bit too long to write as a comment. – Vincent Tjeng Mar 8 '13 at 3:34
I've solved the problem over integer $t$ after some work. – Vincent Tjeng Mar 8 '13 at 5:59

Rearranging, we have

$$xyz-1=zt(x-1)(y-1)-t(x-1)(y-1)$$ $$z\left(xy-t(x-1)(y-1)\right)=1-t(x-1)(y-1)$$ $$z=\frac{1-t(x-1)(y-1)}{xy-t(x-1)(y-1)}=\frac{t(x-1)(y-1)-1}{t(x-1)(y-1)-xy}=\frac{t-\frac{1}{(x-1)(y-1)}}{t-\frac{x}{x-1}\frac{y}{y-1}}$$

Now, since $z>y>x>1$, we have $z \geq 4$, and we must have

$$\frac{t-\frac{1}{(x-1)(y-1)}}{t-\frac{x}{x-1}\frac{y}{y-1}}\geq 4$$

Looking at the terms in the denominator, we have $\frac{x}{x-1} \leq \frac{2}{1}, \frac{y}{y-1} \leq \frac{3}{2}$, since $x\geq 2, y\geq 3$

Thus $\frac{x}{x-1}\frac{y}{y-1} \leq 3$. If $t>3$, the denominator is positive, and we have

$${t-\frac{1}{(x-1)(y-1)}}\geq4\left({t-\frac{x}{x-1}\frac{y}{y-1}}\right)$$ $${-\frac{1}{(x-1)(y-1)}}\geq\left({3t-4\frac{x}{x-1}\frac{y}{y-1}}\right)$$

However, if $t>3$, the RHS is strictly nonnegative, while the LHS is strictly negative. Thus, we reach a contradiction.

Edit: In fact, you can improve the bound slightly and go some way to solving the problem for integer $t$ by considering the following cases.

Firstly, for $t=3$, you can show that


for $x\geq3$. Therefore, for $t=3$, it suffices to check the cases where $x=2$.

Now when we have $t=3, x=2$, the equation simplifies to $(y-3)(z-3)=5$, corresponding to the solution $(x,y,z,t)=(2,3,8,3)$.

Similarly, for $t=2$, it suffices to check the cases $x=2, 3, 4$ or $(x,y)=(5,6)$.

Considering the equation modulo $2$, we can eliminate the cases $x=2,4$. For $x=3$, the equation simplifies to give $(y-4)(z-4)=11$, corresponding to the solution $(x,y,z,t)=(3,5,15,2)$. Finally, we substitute $(x,y)=(5,6)$ into the original equation and obtain $30z-1=40(z-1)$, which has no integer solutions.

Finally, for $t=1$, we can simplify the original equation to the following


But we have $$xy+yz+zx\geq3x+4y+2z>x+y+z$$ Thus there are no solutions to the equation when $t=1$.

To summarize, the two integer solutions for integer t are $(x,y,z,t)=(2,4,8,3) or (3,5,15,2)$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.